Evaluation of Gasket Surface Contact Stress Uniformity Based on Gray-Level Co-Occurrence Matrix - Jiayan Chen; Zhenyu Zhang; Lu Wang; Qiang Wang (Applied Sciences, 2022)
Due to the high demand for compression recovery tests of metal gaskets, it is difficult to provide and evaluate uniform stress on metal gaskets. To effectively evaluate the uniformity of surface stress on a metal gasket, we propose a method of evaluating gasket surface stress based on gray-level co-occurrence matrix theory. Angular second moment and entropy are selected as the main characteristic parameters, and the evaluation indexes (<semantics>f1</semantics> and <semantics>f2</semantics>) are proposed. The analysis is based on finite element calculation under different parameters of a gasket test rig. The angular second moment and entropy curve of the stress distribution cloud map are drawn according to the result of finite element calculation. The results show that the method can evaluate the uniformity of stress distribution. The best parameters of the gasket testing rig are obtained by analyzing the uniformity evaluation index. The method can realize rapid comparison and accurate evaluation of the gasket surface stress.